IMPLEMENTASI METODE AGILE DALAM PENGEMBANGAN APLIKASI BERBASIS WEB UNTUK LATIHAN MEMBER MENU KOFFIE X JOYO GYM 2 - Fakhrur Reza Nursalam; Adis Marhaenisa; Roeslan Djotalov (Journal of Research and Publication Innovation, 2025)
The growing trend of fitness and healthy lifestyles has driven the need for digital solutions that effectively support workout programs. This study explores the implementation of the Agile method in developing a web-based application designed to provide tutorial variations for workout movements tailored for members of Menu Koffie X Joyo Gym 2. The application aims to simplify access to structured workout guides that meet individual needs. Agile methodology was chosen to ensure iterative, adaptive development and the ability to respond promptly to user requirements. The application’s key features include movement variation management, supporting documentation, and integration with member data. Development results demonstrate that adopting Agile facilitates delivering relevant, flexible, and efficient solutions to support modern fitness trends. Thus, this application is expected to enhance members' workout experiences while serving as an effective Agile implementation model for similar projects.